Students’ metacognition growth in reading: the effectiveness of flipped metacognitive strategy - Dina Ramadhanti; Diyan Permata Yanda; Rizki Nofriadi (International Journal of Evaluation and Research in Education (IJERE), 2026)
Metacognitive functions as a means to regulate cognitive abilities, such as reading. The greater a person’s awareness of their metacognitive processes during reading, the more effectively they will comprehend the material. This research aims to assess the effectiveness of a flipped metacognitive strategy (FMS) as a learning approach that incorporates metacognitive skills with a focus on technology in education. A random selection method was employed to choose 28 participants for the study. The findings indicated a notable difference in the average scores of students’ metacognitive awareness before and after the implementation of the FMS. Specifically, metacognitive awareness in reading improved from a score of 56.42, categorized as “good enough”, to 80.79, classified as “very good”. The effectiveness assessment revealed that the N-Gain percent value for students’ metacognitive awareness stands at 54.81%, placing it in the less effective category. Therefore, the FMS can be utilized to enhance metacognitive awareness in reading. Nonetheless, this strategy requires ongoing implementation to be optimally effective in tracking the advancement of students’ metacognitive awareness, particularly in reading. As long as learning strategies are in place, educators must elevate the quality of instructional materials and pay greater attention to the learning needs of students. To enhance reading comprehension, teachers should foster students’ metacognitive awareness, which encompasses understanding various reading strategies, recognizing problem-solving techniques during reading, and being aware of the factors that contribute to reading comprehension.